InterRAI Pediatric Home Care (PEDS-HC) Assessment Tool: Evaluating Ontario Healthcare Workers' Experience. (March 2022) - Lynch-Godrei, Anisha; Doherty, Megan; Vadeboncoeur, Christina
High quality pediatric homecare requires comprehensive assessment of the needs, supports, and health care challenges of children with special healthcare needs and their families. There is no standardized homecare assessment system to evaluate children's clinical needs in the home (support services, equipment, etc.) in Ontario, Canada, which contributes to inequitable homecare service allocation. In 2017, the interRAI Pediatric Home Care assessment tool (PEDS-HC) was implemented on a pilot basis in several regions of Ontario. This qualitative descriptive study explores the experiences of homecare coordinators using the PEDS-HC, seeking to understand the utility and feasibility of this tool through focus group discussion. Four major themes were identified including: the benefits of the tool; areas for modification; challenges to use; and Clinical Assessment Protocols to develop. These themes can guide modifications to the tool to improve utility and improve pediatric home care services. The PEDS-HC is an effective tool to assess children needing homecare in a standardized and comprehensive manner. Use of the tool can improve the quality of homecare services by ensuring equity in service provision and facilitate early identification of clinical issues to prevent unexpected health deteriorations.